Understanding Students Characteristics of Graduates in Biological Education Department (A Case Study Done in Muhammadiyah University Prof. Dr. Hamka) - Maesaroh; Akbar, Budhi; Murwitaningsih, Susanti; Elvianasti, Mega; Aslan (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of this study was to understand the ability of students to conduct experiments in Biology education programs with different educational backgrounds. Descriptive method with quantitative approach was used to analyze data inductively. Determination of the sample with a purposive technique, namely as many as 37 students who took the general Biology course in the 2018/2019 academic year. The results showed that the ability to carry out experimental studies of Biology teacher candidates was 97.6% with an excellent category.There are four aspects of carrying out the experimental study skills analyzed, namely: 1) determining the tools and materials, 2) grouping the data, 3) drawing conclusions, and 4) describing the results of the study. Rating with the lowest score is the skill to describe the results of the study. The ability to carry out experiments is an important part of the scientific method, which in the learning process is used to find concepts, theories or scientific facts through a series of stages of the scientific method such as a scientist in Biology education.